A Silver Yarn-Incorporated Song Brocade Fabric with Enhanced Electromagnetic Shielding - Zhang, Xiuling (Materials (Basel), 2021)
The fabrics with electromagnetic interference (EMI) have been used in various fields. However, most studies related to the EMI fabrics focused on the improvement of the final electromagnetic shielding effectiveness (EM SE) by adjusting the preparation parameters while the breathability of the EMI fabrics was affected and the visible surficial patterns on the EMI fabric was limited. In this work, the two samples based on the Song Brocade structure were fabricated with surficial visible pattern ‘卐’. One was fabricated with silver-plated polyamide (Ag-PA) yarns and the silk yarns, the another with polyester (PET) yarns and the silk yarns. The weaving structure of the two samples were investigated by scanning electronic microscopy (SEM) and laser optical microscopy (LOM). The resistance against the EM radiation near field communication (NFC) and the ultraviolet (UV) light was also evaluated. Besides, the surface resistance, the air permeability and the water evaporation rate were investigated. The results revealed that the ‘卐’ appeared successfully on the surface of the two samples with stable weaving structure. The Ag-PA yarn-incorporated Song Brocade fabric had the EMI shielding effectiveness value around 50 dB, which was supported by the low surface resistance less than 40 Ω. The excellent NFC shielding of the Ag-PA yarn-incorporated Song Brocade was also found. The ultraviolet protection factor (UPF) value of the Ag-PA yarn-incorporated Song Brocade fabric was higher than 190. The air permeability and the evaporation rate of the Ag-PA yarn-incorporated Song Brocade fabric was higher than 99 mm/s, and 1.4 g/h, respectively. As a result, the Ag-PA yarn-incorporated Song Brocade fabrics were proposed for both the personal and the industrial scale utilization.